Plans of KGB on the even of Lithuania independance 70th anniversary - Anušauskas, Arvydas (Genocidas ir rezistencija, 1998)
A few months after the first public commemoration of the ‘Black Ribbon Day’ at the monument to Adomas Mickevičius (23 August 1987), the KGB started its arrangements for a new wave of protests in the run–up to 16 February 1988. On 1 February 1988, the KGB’s 5th Unit in charge of combating ideological opponents, drafted a note titled “On the hostile aspirations and tendencies of foreign emigrants and other anti–Soviet centres against the Lithuanian SSR”. The continued non–recognition of the incorporation of the Baltic states into the Soviet Union was also seen as a major stimulus to the activities of the liberation organisations. The question of how to prevent the influence of the free world became a decisive factor in the organisation of KGB activities. This is also evident from the document published below.
Keywords: KGB; emigree; antisoviet resistance